Formas de fósforo em solos de uma toposequência de Viçosa, Zona da Mata, Minas Gerais - Dutra, Leôncio G; Braga , José Mário (Revista Ceres, 2025)
This research was conductes in order to obtain data about phosphorus forms and contents in soil plotted in a topographic sequence at Viçosa, Minas Gerais. Samples of open profile horizons were taken following a topographic sequence, and determinations of inorganic phosphorus fractions were made for these samples. Fractions separated were as fractions: water soluble forms, forms adsorbed on aluminum, form adsorbed on iron, forms soluble in a reducing agent, and forms occluded in iron and aluminum.